Pengaruh Daya Ledak Otot Tungkai terhadap Hasil Lari Sprint 100 Meter melalui Program Latihan Naik Turun Tangga pada Siswa SMA Wachid Hasyim 7 Surabaya - Rakhma Indah Notafiah; Sri Wicahyani (MAN Insan Cendekia Jambi, 2026)
This study aimed evaluate the effect of lower-limb explosive on 100-meter sprint performance through a stair climbing and descending training program among students of Wachid Hasyim 7 Senior High School Surabaya. The background of this study stems from the fact that students' sprinting abilities had not yet reached an optimal level due to a lack of structured and systematic training. A quantitative approach was utilized in this study, applying a quasi-experimental method through a one-group pretest-posttest design. A total of 30 students were selected as the research sample through purposive sampling. Data were collected using the vertical jump test and the 100-meter sprint test. The data were analyzed using a paired-sample t-test. The findings revealed a significant improvement in sprint performance, as indicated by a decrease in the average sprint time from 26.49 seconds to 22.93 seconds. A significance value of less than 0.05 and an effect size of 0.842 demonstrated a strong statistical and practical effect. The study indicates that stair climbing and descending exercises can significantly enhance lower-limb muscle power and improve sprinting performance.